Padawan - White, Kiersten (Star Wars, 2022)
Obi-Wan Kenobi has not been apprenticed long to Qui-Gon Jinn, and he is chafing at Qui-Gon's training style: all meditation, no action. Obi-Wan yearns to prove himself on a mission, but when he and Qui-Gon are finally set to leave on an assignment, Qui-Gon is nowhere to be found. Angered by his master's abandonment, Obi-Wan sets out on the mission alone, determined to prove himself. On a mysterious planet he encounters a pack of feral, Force-wielding teens who seem to be the planet's only inhabitants. As he experiences wild freedom with them and wonders if this isn't the life he was meant for, Obi-Wan can't escape the nagging sense that something is wrong with the Force there. Growing attachments, startling revelations, and a looming threat to both the planet and his new friends will bring Obi-Wan face-to-face with his worst fear: that maybe he was never supposed to be a Jedi at all. Can he connect with the living Force in time to save himself and everyone around him? It's the star of the Obi-Wan Kenobi Disney+ limited series as you've never seen him before...